Modern State and Efficiency Analysis of Heat Recovery in Fuel Furnaces Using High Temperature Recuperators. Part 2 - B. S. Soroka; V. A. Zgurskyi; N. V. Vorobyov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper analyzes various factors that affect upon heat transfer in high temperature recuperators, namely: heat transfer enhancement, heat exchange surface increase and rise of temperature head between primary and secondary heat transfer fluids. Comparison of experimental data with the results of mathematical and computational fluid dynamics (CFD) modeling has been performed in the paper. The paper considers some new designs of high temperature heat recovery plants: tube recuperator equipped with internal inserts – secondary emitters inside tubes for metallurgical furnaces and high-efficient two-way radiative recuperators for machinery engineering furnaces.  Advantages of new recuperators in comparison with existing analogues have been estimated in the paper. These advantages are:  provision of additional fuel saving due to increase of preheating temperature of the combustion air and improvement of design stability by decrease of tube wall temperature.